2004
DOI: 10.1023/b:caco.0000036173.99930.75
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Developing Hepatocellular Carcinoma Associated with Carriage of the TNF2 Allele of the -308 Tumor Necrosis Factor-α Promoter Gene

Abstract: Carriage of the TNF2 allele is a significant predictor of HCC independent of hepatitis B and C, and therefore it may be used as a biomarker for susceptibility to HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 32 publications
2
40
0
1
Order By: Relevance
“…In a study by Kakumu et al TNF-αRs correlated with disease progression and IFN-α treatment did not affect their level (162). Regardin TNF-α polymorphism, the TNF-α (-308) SNP (single nucleotide polymorphisms) in the promoter region of the gene, which includes TNF-α1 (-308G) and TNF-α2 (-308A) alleles, is associated with cancer susceptibility and induced expression of TNF-α (153,(165)(166)(167).…”
Section: Hepatic Stellate Cells (Hscs)mentioning
confidence: 99%
“…In a study by Kakumu et al TNF-αRs correlated with disease progression and IFN-α treatment did not affect their level (162). Regardin TNF-α polymorphism, the TNF-α (-308) SNP (single nucleotide polymorphisms) in the promoter region of the gene, which includes TNF-α1 (-308G) and TNF-α2 (-308A) alleles, is associated with cancer susceptibility and induced expression of TNF-α (153,(165)(166)(167).…”
Section: Hepatic Stellate Cells (Hscs)mentioning
confidence: 99%
“…The etiological factors involved in HCC are well known (Ho et al 2004), but genetic factors of HCC have been incompletely understood, which has been postulated to inXuence the progression of HCC. Because risk for HCC increases with the severity of hepatic inXammation and chronic inXammation developing through the action of various inXammatory mediators is known as a cofactor of carcinogenesis (Coussens andWerb 2002, Tarao et al 1999), among inXammatory mediators, pro-inXammatory cytokine, TNF-has been postulated to have a crucial role in the pathogenesis of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In a case study in Taiwan, the authors concluded that carrying the TNF2 allele is a significant predictor of HCC independent of hepatitis B and C, and therefore that it may be used as a biomarker for susceptibility to HCC (12). Several polymorphisms of proinflammatory IL-1Β have been reported, and the IL-1B-31 the IL-1B-511 genotypes have been associated with enhanced IL-1B production.…”
Section: Tnf-α -863 Polymorphisms and The Risk Of Hepatocellular Carcmentioning
confidence: 99%